Determining difference from disability what culturally responsive teachers should know - McCain, Gerry; Farnsworth, Megan (Routledge, 2018)
"This essential book offers clear guidelines for determining if the Culturally Linguistically Diverse (CLD) students / English Language Learners (ELL) in your general education classroom are experiencing typical language differences, learning disabilities, or both. By combining helpful case-studies with insightful research, the authors provide a framework for differentiating instruction that uses culturally appropriate interventions to build upon student strengths while creating a foundation for further learning and achievement."--Provided by publisher.